1970
DOI: 10.1152/ajplegacy.1970.219.1.246
|View full text |Cite
|
Sign up to set email alerts
|

Effects of endotoxin on distribution of cardiac output in unanesthetized rabbits

Abstract: The APS Journal Legacy Content is the corpus of 100 years of historical scientific research from the American Physiological Society research journals. This package goes back to the first issue of each of the APS journals including the American Journal of Physiology, first published in 1898. The full text scanned images of the printed pages are easily searchable. Downloads quickly in PDF format.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
9
0

Year Published

1973
1973
2014
2014

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(10 citation statements)
references
References 0 publications
1
9
0
Order By: Relevance
“…The regional vascular responses in the present experiments under prolonged moderate hypoxia are comparable to those seen after a reduced cardiac output from hemorrhage or endotoxic shock [11,14,24,31]. This is not surprising since the cardiovascular adjustments, i.e., the balance between enhanced adrenergic activity and local flow regulation, serve to divert blood predominately from the kidneys in order to provide a greater blood supply to the vital organs represented by the brain, the heart and possibly also by the skeletal muscle.…”
Section: Discussionsupporting
confidence: 74%
“…The regional vascular responses in the present experiments under prolonged moderate hypoxia are comparable to those seen after a reduced cardiac output from hemorrhage or endotoxic shock [11,14,24,31]. This is not surprising since the cardiovascular adjustments, i.e., the balance between enhanced adrenergic activity and local flow regulation, serve to divert blood predominately from the kidneys in order to provide a greater blood supply to the vital organs represented by the brain, the heart and possibly also by the skeletal muscle.…”
Section: Discussionsupporting
confidence: 74%
“…Indeed, Wyler et al reported that a high-dose bolus injection of LPS produces a rapid cardiovascular collapse and early death. 17 Basically, a prolonged infusion of a low dose of bacteria limits the appearance of the cardiovascular collapse in small or large animals.…”
Section: Discussionmentioning
confidence: 99%
“…The evidence from the present experiments suggests that the increased sympathetic discharge maintains myocardial contractility (increased dP/dt max at the same LVEDP) well into the shock period but that output is reduced because of the lowered venous return. Although there is some disagreement in the literature (see Introduction), some recent evidence appears to demonstrate that endotoxin does have a direct myocardial depressant effect (Solis & Downing, 1966;Wyler, Neutze & Rudolph, 1970). In vivo, this appears to be balanced by the effect of released catecholamines; if the myocardial effects of catecholamines are prevented by 8-adrenoceptor blockade, at least in the early stage of shock, myocardial contractility is not maintained and the animals die in right ventricular failure.…”
Section: Discussionmentioning
confidence: 99%